Reinforcement of Slope Failure on Ponorogo – Pacitan KM 226 Road to Mitigate Landslides - Akbarrina, Ailia Rizky; Zaika, Yulvi; Rachmansyah, Arief (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
Slope collapse can be caused by changes in load or geological conditions of the soil. Slope collapse events often occur during the rainy season in the Ponorogo area, Pacitan East Java, Indonesia, which causes closed transportation to and out of the Ponorogo area. This study aims to investigate the failure mechanism and landslide mitigation. The field investigations were conducted using geoelectricity and soil sampling to be analyzed in the laboratory. This research employed the Schlumberger geoelectrical configuration method to determine the subsurface rock lithology arrangement. The study involved acquiring data on four geoelectrical lines with a length of 135 meters. The collected field data was then processed and modeled to obtain an overview of the subsurface rock lithology arrangement. The Laboratory tests were conducted to determine the soil type and the soil parameters unit weight (?), cohesion (c'), and shear angle (?'). The laboratory data was input into software to obtain the safety factor. The geo-electrical results showed layers of clay and tuff, which identified a water flow between them, the landslide plane. Based on the finite element analysis, the landslide planes were almost coincident. Slope stability is achieved by changing the geometry and reinforcing it with piles.